The Role of Government Cash Subsidy Assistance, Entrepreneurship Orientation and Product Innovation on the Performance of MSMEs in Gelamjaya Village, Pasar Kemis, Tangerang Regency - Verry Cyasmoro (Enrichment : Journal of Management, 2021)
MSMEs, or Micro, Small and Medium-Sized Enterprises, make a major contribution to Indonesia. The MSME sector accounts for the majority of the Indonesian economy. Even several times, the economic downturn that afflicted the global MSME sector should have survived the 1998 and 2008 monetary crises, as well as the current COVID-19 pandemic. Due to this sector's resistance, the government has committed to providing stimulus in the form of subsidies through the national economic recovery program. The aim of this study is to ascertain the effect of government cash subsidies, entrepreneurial orientation, and product innovation on the output of micro, small, and medium-sized enterprises (MSMEs). The study used a quantitative approach, which included data collection directly from 100 participants from MSME actors in the village of Gelam Jaya, Tangerang Regency. The findings indicate that government cash subsidies have a partly positive, significant influence on MSME's performance; business opportunities have a partly positive, significant impact on the MSME's performance; product innovation has partly a positive and significant effect on MSME's performance; and government cash subsidies, business orientation and the situation is significant.